Towards a fairer and more ‘tika’ political science and politics: Are political science programs equipping students adequately for Aotearoa realities? - Te One, Annie; Bargh, Maria (The Australian Journal of Indigenous Education, 2023)
Social and political change is occurring in Aotearoa New Zealand and tikanga, mātauranga, te reo Māori (the Māori language) and Te Tiriti o Waitangi (Treaty of Waitangi) are increasingly being recognised in diverse political and legal contexts. This article explores whether the political science discipline is keeping pace with these political changes, whether research and course content is adequately reflecting these new realities, and if students are appropriately equipped to participate. In particular, we examine the state of university politics programs and outline the form and quantity of Māori politics in the teaching and research of these programs. From the assessment of the current state of politics programs, we make some observations about what changes may be required to ensure politics programs, their students and academics are fully equipped to work in the unique political and legal landscape of Aotearoa New Zealand. Approximately 1% of political science lecturers are Māori, 1% of content taught can be classified as Māori politics and approximately 1% of publications in the New Zealand Political Science journal can be classified as kaupapa Māori politics. This 1–1–1 crisis provides a bleak picture of the existing arrangements in politics programs in Aotearoa New Zealand and must change.